(3x)1/3 appears to be (3x)*(1/3), which is simply x because the 3's in the numerator and denominator cancel out. So you just have x = 2, which is your answer.
2007-03-18 03:56:20
·
answer #1
·
answered by DavidK93 7
·
1⤊
0⤋
3x *1/3 = 2
You can cancel both the 3's because one 3 is in the numerator and the other is in the denominator.
They become 1.
Therefore u are left with x *1=2
Therefore x = 2
To verify substitute x = 2 on the left hand side (LHS):
Therefore, 3*2*1/3 = 2
3 and 3 get cancelled and u get 2=2. There you go.
2007-03-18 04:11:42
·
answer #2
·
answered by Drools over home made food 6
·
0⤊
0⤋
x=2
verification (3*2)/3 = 2
2007-03-18 03:58:58
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
(3x)1/3 = 2
(3x)3(1/3) = 3(2)
3x = 6
3x / 3= 6 / 3
x = 6 / 3
x = 2
- - - - - - - -s-
2007-03-18 04:18:58
·
answer #4
·
answered by SAMUEL D 7
·
0⤊
0⤋
(3x)1/3 = 2
3x/3 =2
the 3's cancel, so
x=2
2007-03-18 03:59:59
·
answer #5
·
answered by jaybee 4
·
0⤊
0⤋
x both sides by 3
(3x).(1/3).(3) = 6
3x = 6
x = 2
2007-03-18 04:05:09
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
(3x)1/3=2
or, (3x)*1/3=2
or, (3x)/3=2
or, x=2
2007-03-18 03:57:25
·
answer #7
·
answered by Bubblez 3
·
0⤊
0⤋